Effect of three protocols of warming up involving stretching on the kinematic performance of horizontal jumping, agility and speed for soccer players - Abdelkader, M. A.; Elmorsi, W. M. (American Journal of Sports Science, 2016)
The aim of this study is to investigate the effect of three different protocols of stretching on the kinematic performance of horizontal jumping, Agility and speed for soccer players. The first protocol is doing ballistic stretching then static stretching exercises (BS-SS). The second protocol is doing static stretching then ballistic stretching exercises (SS-BS). The third protocol is doing soccer passing drills (SPD) for 10 minutes without stretching. The three protocols were applied after 5 minutes of running activities. Dependent variables included a horizontal jump, agility run, and 30-m sprint tests. Also speed, acceleration, and steps frequency were analyzed. This study was applied on 23 trained male student-athletes aged (20+ 0.4 years). The (SS-BS) condition (2.247 + 0.096 m) showed significant differences (p < 0.01) for longer distance than the (BS-SS) condition (2.165 + 0.124) and also than the (SPD) condition (2.197 + 0.110 m) in the horizontal jump test. The (SS-BS) condition (3.544 + 0.247 second) also showed significant differences (p < 0.01) in the flying 30m sprint test for faster times than the (BS-SS) condition (3.858 + 0.288 second) and also than the third condition (SPD) (4.050 + 0.193 second) . The (SPD) condition showed significant differences (p < 0.01) in agility test for faster time than both the (BS-SS) (11.533 + 0.485) and (SS-BS) (11.676 + 0.530) conditions. Depending on the study results and previous studies, (SS-BS) which may be practiced before high intensity activities in trained athletes if preceded by moderate intensity running activities is recommended.